Audit Sistem Informasi Menggunakan Framework Cobit 5: (Studi Kasus : PT Media Cetak) - Eninta Rahayu Barus; Elfira iriani; Fresti anjeli (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The information systems currently used by PT Media Print need to be evaluated to ensure that they remain relevant, efficient and secure. In the competitive print media industry, it is important for companies to ensure that their information systems support business processes well and provide high-quality service to customers. This audit aims to ensure that the information system functions properly, protects sensitive information, and meets organizational goals. By using an information system audit, it is hoped that it can help identify areas where improvements or improvements are needed to improve service quality and control existing security in information systems, including access management, data encryption, user activity monitoring, and data protection measures. From the research carried out, the final result was obtained, namely DSS03 (Manage Service Requests and Incidents) showing the overall level of capability in the DSS03 sub-process and the average results for the DSS03 IT Process itself are shown in table 3 process capability domain DSS03 manage operations.